42PPrediction of PFS using a dynamic assessment of ctDNA in patients with EGFR mutated NSCLC with osimertinib therapy. (7th November 2019) - Moiseenko, F; Stepanova, M; Zhabina, A; Myslik, A; Klimenko, V; Rysev, N; Artemieva, E; Shelekhova, K; Bogdanov, A; Volkov, N; Moiseenko, V
Abstract: Background: Resistance on the 1st or 2nd generation TKIs in patients with EGFR mutated NSCLC to the therapy occurs on average after 8-12 months. The most common (49-60%) resistance mechanism is the appearance of the T790M. Its determination is possible by different methods of examination: ctDNA (false-negative probability 23%) and tumor tissue (sensitivity of 88%). The appointment of osimertinib in the second line allows to increase ORR, but also PFS relative to standard chemotherapy. Methods: In this study we investigated the effect on PFS by the dynamic determination of ctDNA. Included patients with metastatic EGFR-associated NSCLC, in whom, a T790M mutation was detected during treatment TKIs of 1-2 generations.Patients received osimertinib therapy 80 mg / day, daily, until progression of the disease appears. Blood test was taken to conduct a qualitative assessment of ctDNA in dynamics by the RT-PCR method, fist test was done before starting treatment, and then every 2 months. Results: From August 2016 to December 2018, 22 patients were identified T790M + associated progression of EGFR + NSCLC. 81.9% (18/22) are women, 18.1% (4/22) are men. The average age is 61.2 years (50-75). 1/22 had smoking experience for more than 30 years. The molecular genetic profile in 16 is represented by ex19del, 5 L858R, 1 - a combination of rare mutations G719S + S768I. The effect of therapy was evaluated in 20/22 patients. PR and SD were registered in 9/20 (45%) and 10/20 (50%) patients, respectively. Median PFS – 18.9 months (CI 95%, 10.6 - 27.1). In 12/22 patients was observed the disappearance of ctDNA T790M + after 2 months of osimertinib therapy. PFS is 24.4 months (CI calculation is NA), in patients with no mutation detected in the second month of treatment compared with the group of patients in which the ctDNA was determined (PFS 7.6 months) (CI 95%, 3.0 –12.9) (p = 0.003). The confidence interval for one of the medians cannot be calculated the 75% percentile was 3.4 +/- 3.3 and 18.8 +/- 6.3. Conclusions: The disappearance of ctDNA in plasma after 2 months of treatment with osimertinib is associated with an increase in PFS and can be considered as a predictive marker in patients with metastatic NSCLC EGFR T790M + Grant supported RUSSCO / RakFond 2018-01-YS-ECI. Legal entity responsible for the study: St. Petersburg Clinical Research Center of Specialized Types of Care (Oncology). Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.